2019
DOI: 10.2486/indhealth.2018-0159
|View full text |Cite
|
Sign up to set email alerts
|

Burnout syndrome in Europe: towards a harmonized approach in occupational health practice and research

Abstract: Health practitioners and decision makers in the medical and insurance systems need knowledge on the work-relatedness of burnout. To gather the most reliable information regarding burnout diagnosis and recognition in Europe, we used an 8-item standard questionnaire sent by e-mail to occupational health specialists identified via the Network on the Coordination and Harmonization of European Occupational Cohorts (OMEGA-NET) within the European Cooperation in Science and Technology (COST) Action. Participation rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 21 publications
(28 reference statements)
1
27
0
Order By: Relevance
“…If accepted more generally, this definition may reduce the semantic chaos surrounding the concept of occupational burnout and improve medical research, treatment and prevention of this outcome. It may also clarify whether burnout should be classified as a disease (6,46). In SNOMED-CT, 'burnout' is classified under the clinical finding hierarchy, which only includes concepts that refer to diagnoses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If accepted more generally, this definition may reduce the semantic chaos surrounding the concept of occupational burnout and improve medical research, treatment and prevention of this outcome. It may also clarify whether burnout should be classified as a disease (6,46). In SNOMED-CT, 'burnout' is classified under the clinical finding hierarchy, which only includes concepts that refer to diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…The latter method was implemented through the national focal points of the European Agency for Safety and Health at Work (EU-OSHA) (22) and OMEGA-NET members, who we asked to identify at least one health practitioner in each of the 33 OMEGA-NET participating countries (16). We used this approach previously (6) and found it effective. The working language was English.…”
Section: Consensus Search Through the Delphi Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported that work-related stress is a trigger for mental disorders (specifically depression [ 14 , 20 , 21 ], sleep disorders [ 22 , 23 ], heart and/or respiratory diseases, and physical or cognitive fatigue [ 24 , 25 ]. Moreover, if work-related stress is prolonged and worsened over time, it can lead to burnout in the worker [ 26 , 27 ]. Burnout was defined by Maslach, Schaufeli, and Leiter as “a prolonged response to chronic emotional and interpersonal stressors at work, defined by the dimensions of exhaustion and inefficiency” [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…In order to remedy this situation, we have established a general reference framework for the validation process of diagnostic tools for mental disorders, including self-reported measures of burnout. The burnout syndrome remains ill-defined and nosologically uncharacterized (15). Despite its increasing importance (16), burnout syndrome still has no consensual definition, which makes it difficult to manage.…”
Section: Introductionmentioning
confidence: 99%